2014
DOI: 10.1021/je500185r
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Imidazolium-Based Ionic Liquids: The Effect of Aliphatic versus Aromatic Functionality

Abstract: Synthesis of 1-(cyclohexylmethyl)-3-methyl imidazolium bis[(trifluoromethane)sulfonyl]amide ([CyhmC 1 im][NTf 2 ])A one-neck round bottom flask, under nitrogen, equipped with a magnetic stirrer and a condenser, was charged with 1-methylimidazole (6.65 g, 81.02 mmol). To this mixture, an excess (1.05 eq.) of (bromomethyl)cyclohexane (15.06 g, 85.07 mmol) was added. The reaction was left under constant stirring at 50 °C, until complete consumption of the 1-methylimidazole.The 1-(cyclohexylmethyl)-3-methylimidazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 35 publications
5
47
0
Order By: Relevance
“…Similar results were also obtained by Tao et al who observed that in imidazolium based ILs the presence of the cycloalkyl group in place of the n-alkyl group with the same number of carbons leads 75to an increase in density 49. This confirms that this AA anion…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were also obtained by Tao et al who observed that in imidazolium based ILs the presence of the cycloalkyl group in place of the n-alkyl group with the same number of carbons leads 75to an increase in density 49. This confirms that this AA anion…”
supporting
confidence: 88%
“…We think that the insertion of the amino group in the ring structure constrains the alkyl portion in such a way that it cannot form well separated hydrophobic domains as observed for alkyl chains. 39 49 The authors concluded that the density trend could be roughly related to the C/H ratio in the substituents, with density increasing with increasing C/H ratio from n-alkyl, cycloalkyl, to aromatic functionalities. Stacking interactions could also 15 contribute to the packing of the phenyl substituents and, eventually, to their segregation in hydrophobic domains decreasing the density.…”
Section: Density Measurementsmentioning
confidence: 99%
“…Most studies on physical properties at various temperatures have focused on imidazolium cations [18,21,22], other families of cations have been less extensively studied. In particular reports on the physicochemical properties of morpholinium based ILs are scarce [23,24].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The synthesized IL was characterized by 1 H NMR, 13 C NMR and FTIR spectroscopic techniques. The 1 H NMR and 13 C NMR of synthesized IL were recorded on Brukar Avance 500 MHz spectrometer using CDCl 3 as solvent and TMS as the internal standard.…”
Section: Synthesis and Characterization Of 1-butyl-3-methylimidazoliumentioning
confidence: 99%
“…One of the most extensively studied class of ionic liquids are those based on imidazolium cation [5,[13][14][15][16][17][18]. In 2002, Swatloski et al [14] used imidazolium based IL for the dissolution of cellulose, since then the use of ILs particularly imidazolium based ILs for the biomass dissolution and conversion of biomass to biocompatible or biodegradable materials has attracted both academic and industrial interests [19][20][21].…”
Section: Introductionmentioning
confidence: 99%